Early Middle Adolescents and Quran Memorizers: How Does Social Penetrationn Work? - Ariibah, Fathiyya Khonsa (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
This study describes the process of social penetration of musyrifah (mentor) and female students in an effort to increase memorization at the Miftahunnajah Islamic Boarding School, and determines the factors influence the self-disclosure of female students to musyrifah. Talking about Islamic boarding schools, ideally a female student will be instilled with Islamic values and morals attached to them. The female students who are fostered in Islamic boarding schools are also not free from the label of being able to memorize the Qur'an. The community believes that Islamic boarding schools are the most ideal place to memorize Qur’an. However, the reality is that Islamic boarding schools, which are believed to be the most ideal places to study and memorize the Qur'an, do not guarantee that all students will succeed in memorizing the Qur'an according to the set targets. Through the role of Musyrifah who acts as a companion as well as a role model, it is expected that female students can realize good morals in their lives. This study used Altman and Taylor's theory of social penetration and self-disclosure. The data collection was carried out using qualitative methods with data collection techniques of interviews, observation, and documentation. The research findings show that the social penetration of musyrifah and female students has been stable. This has an important influence in efforts to increase memorization. Meanwhile, the factors that influence self-disclosure of female students to their musyrifah include five important factors, namely, feelings of liking, dyadic effect, personality, topic, and age. This research also results in theoretical and practical implications related to the social penetration of musyrifah and female students in increasing memorization.